The Purpose and Boundaries of the History of Psychology - Petrosyan, Gagik (Bulletin of Yerevan University E: Philosophy, Psychology, 2016)
The discussion of philosophical and methodological issues of psychology based on the history of psychology which provides the substantial basis of such researches. However, not every “history of psychology” can handle these tasks. How should be the "history", which underlies the philosophical and methodological researches? The article discusses the criterion and possibility of reconstructing the effective history of psychology.